Pembelajaran Bahasa Inggris Berbasis Bisnis Pariwisata: Upaya Pemberdayaan Masyarakat Berbasis Komunitas - Ima Frafika Sari (The Indonesian Institute of Science and Technology Research, 2022)
The Community Dedication activity is an activity to help other communities in certain situations without expecting anything in return. This dedication activity is carried out using a participatory action research (PAR) approach in the tourism sector in Goa Gong Pacitan. This activity uses 3 stages in its implementation namely preparation, implementation of activities, and evaluation of activities. The target of this activity is the people around Goa Gong Pacitan who work as tour guides and who have other livelihoods. The aims of this activity is to improve the ability of English speaking for the people around Goa Gong Pacitan, and to provide the motivation and awareness to the people around tourist attractions in learning English. This article is a kind of qualitative describing and explaining descriptively. The result of this activity is the training participants can learn English well, they can understand teaching techniques both in terms of context and vocabulary of English, there is a sense of confidence in communicating using English, the availability of training places, and the availability of a place for coordination/deliberation.